Production of Green Banana Powder Sauce from Ambul and Puwalu Varieties and Evaluate their Physicochemical, Antioxidant Properties and Shelf Life - Galagedara, G.M.S.N.; Sarathadevi, R.; Vasantharuba, S. (Proceedings of the Annual Scientific Sessions of the Nutrition Society of Sri Lanka - 2022, 2022)
The goal of this research was to make green banana sauce from Ambul and Puwalu banana varieties harvested in Kilinochchi, Sri Lanka, and to evaluate their antioxidant properties (total phenolic content (TPC), total flavonoid content (TFC), and antioxidant capacity), proximate composition and shelf life. The green banana powder was prepared from the peeled off fresh green banana, and then the sauce was developed according to SLS modification made to the SLS 581:2008. After several preliminary trials, the best four sauce formulations with control sauce were selected. The green chili sauce was prepared as the control sauce, and the green chili paste was added as a coloring agent for green banana sauce due to the color resemblance with green chili sauce. The 15 g of Ambul green banana powder sauce demonstrated the highest sensorial features followed by 10 g Puwalu sauce; 250 g sauce was made from this powder formulation. Overall, the proximate composition of the selected two sauces was higher than the control sauce on a fresh weight basis. Among, the crude protein (4.37-5.03%), crude fiber (24.34- 23.35%) and ash content (2.2-2.64%) were significantly (p<0.05) higher than the control sauce (Crude protein 1.24%, crude fiber-6.75% and ash – 1.27%). Extraction was carried out with 70% (v/v) ethanol to determine the antioxidant properties. The TPC (0.09 mg of Gallic acid equivalent/ g dry matter) and antioxidant capacity (0.115 mg of Catechin equivalent/ g dry matter,) were high in the Puwalu sauce than Ambul sauce (TPC- 0.057 mg of Gallic acid equivalent/ g dry matter, and antioxidant capacity- 0.113 mg of Catechin equivalent/g dry matter,). However, the TFC was significantly (p<0.05) higher in the Ambul sauce (0.152 mg of Ascorbic acid equivalent/g dry matter) than Puwalu sauce (0.101 mg of Ascorbic acid equivalent/g dry matter). For shelf-life analysis, after one and two months of storage, both sauce samples reported total plate count was lesser than 10 (2-2.5), when compared with the control sauce, the count was 3.2-3.3. As a result, Ambul and Puwalu green banana varieties could be used to make the sauce with profound health benefits.
Keywords: Ambul and Puwalu banana; Antioxidant properties; Green banana powder; Sauce